Peran Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan Sekolah - Sukmadewi, Ni Kadek Diah (Metta : Jurnal Ilmu Multidisiplin, 2022)
Schools are formal institutions that have a high level of urgency and receive attention from the local community regarding the education of the nation's children, so the leadership of the school principal remains the focus of research. Quality education is able to produce graduates who have skills or competencies, both personal and social competencies, as well as academic and professional competencies that are based on noble moral values. The principal has the highest power and authority as a leader and has the ability to organize and develop his subordinates professionally. The school principal is one of the determining factors for the success and quality of a school. The objectives of this research are to describe the role of school principals in improving the quality of school education. The research method used is qualitative research using library research. This type of library research research is by looking at a theory or study from library sources. This research was carried out by reading, reviewing and analyzing various existing literature, in the form of books, articles and research results. The quality of education is an issue that is considered the main problem in education development policy. Because only quality education will produce quality graduates who are able to further develop themselves, their families, their communities, their nation and their nation. The role of the school principal in improving the quality of education is: the principal as a manager, the principal as an administrator, the principal as a supervisor, the principal as an educator, the principal as a leader, and the principal as a motivator. The role of the school principal as a driving force is very important, where the principal as the leader of the educational institution at the school will be a guide driving the school community to carry out activities, improve school infrastructure, increase teacher competence to make changes towards better and higher quality.